How Bibliometric Analysis Using VOSviewer Based on Artificial Intelligence Data (using ResearchRabbit Data): Explore Research Trends in Hydrology Content - Rochman, Syaiful; Rustaman, Nuryani; Ramalis, Taufik Ramlan; Amri, Khairul; Zukmadini, Alif Yanuar; Ismail, I.; Putra, Apriza Hongko (Universitas Pendidikan Indonesia (UPI), 2024)
The purpose of this study was to analyze and map research in hydrology content. We reviewed 45 articles related to hydrology content published from 2014 to 2024. There are several previous literature review studies analyzing hydrology in engineering. However, we have not found any studies that investigate the projects, topics covered, and benefits of implementing hydrological processes in science education. The research method used was a systematic and bibliometric literature review using VoSviewer with ResearchRabbit database. This study analyzed content characteristics based on publication year, publication type, country of implementation, research approach, education stage, and hydrology content. The findings show that VoSviewer with ResearchRabbit database can be used as a research mapping baseline. In addition, the authors found that hydrological content varies according to the topic discussed, but very few found hydrological studies in the social field, especially education. The benefits of implementing educational hydrology in science education include cognitive benefits, procedural benefits (skills), attitudinal benefits, or a combination of the three benefits.